(untitled) (Journal of Pharma Insights and Research, 2025)
A quantitative cross-sectional study was conducted from March to May 2025 to study over-the-counter (OTC) medication usage patterns among 2,000 Indian consumers aged 15 years and above. Data collection utilized a validated online questionnaire covering demographics, knowledge levels, usage behaviors, and safety practices. Results revealed that 71% of participants had used OTC medications within six months, predominantly analgesics (56%), antipyretics (43%), and antacids (39%). While 68% demonstrated moderate awareness of OTC drug safety, critical gaps emerged in safety practices - only 32.7% regularly verified expiry dates, and 27% who experienced adverse effects did not seek medical consultation. Urban residents and those with higher education levels showed significantly better knowledge scores (p < 0.05). The study identified concerning trends: 50.6% never consulted healthcare professionals about OTC use, 24.6% procured medications through online platforms, and 48.6% reported experiencing adverse effects. It is worth noting that only 32.8% consistently read medication labels, and 33.4% never checked usage instructions. Market analysis indicated strong brand preferences, with Dolo (21.1%), Crocin (21.0%), and Digene (20.6%) emerging as leading choices. The results indicate substantial gaps in consumer awareness and safety practices, necessitating enhanced regulatory oversight, structured public education programs, and increased pharmacist involvement in OTC medication counseling